Frost Damage of Carinata Grown in the Southeastern US - Michael J. Mulvaney; Ramdeo (Andy) Seepaul; Ian M. Small; David L. Wright; Silvana V. Paula-Moraes; Carl Crozier; Paul Cockson; Brian Whipker; Ramon Leon (EDIS)
Brassica carinata is an annual oilseed crop used for the commercial production of jet fuel. One of the challenges to commercialization of this crop in the southeastern United States has been frost damage. This 4-page fact sheet discusses symptomology and ways to minimize risk of frost damage to carinata. Written by Michael J. Mulvaney, Ramdeo Seepaul, Ian Small, David Wright, Silvana Paula-Moraes, Carl Crozier, Paul Cockson, Brian Whipker, and Ramon Leon, and published by the UF/IFAS Agronomy Department, May 2018. https://edis.ifas.ufl.edu/ag420